User Preferences With Urgent-Time Intervals in a Wireless-Network - Alquhayz, Hani (Communications in Mathematics and Applications, 2019)
This paper focuses on a scheduler component in a wireless network, with constraints based on user preferences. These constraints reflect the fact that users wish to privatize networks for fixed periods (intervals) in order to send urgent data. The user sets in advance certain data constraints and time periods. Each time period is presented as a frozen interval for the router and other users. Only the administrator can send data during these specifics periods and all others users will be frozen. During this interval, the intelligencer can send confidential and emergency data without any concurrency with other data through this interval, which is called an "emergency and secret interval”. Each time, a scheduling problem due to unavailable machines and jobs will be solved. This problem is NP-hard. In this research, we develop two algorithms for transmitting data from the sender to the receiver.
Keywords: Data transmission; Wireless network; Packets; Heuristics; Scheduling into networks